Immune microenvironment and immunotherapy in hepatocellular carcinoma: mechanisms and advances - Xie, Dong; Liu, Yang; Xu, Fangbiao; Dang, Zhibo; Li, Mengge; Zhang, Qinsheng; Dang, Zhongqin (Frontiers in Immunology, 2025)
Hepatocellular carcinoma (HCC) remains a leading cause of cancer-related mortality globally. The tumor microenvironment (TME) plays a pivotal role in HCC progression, characterized by dynamic interactions between stromal components, immune cells, and tumor cells. Key immune players, including tumor-associated macrophages (TAMs), tumor-infiltrating lymphocytes (TILs), cytotoxic T lymphocytes (CTLs), regulatory T cells (Tregs), MDSCs, dendritic cells (DCs), and natural killer (NK) cells, contribute to immune evasion and tumor progression. Recent advances in immunotherapy, such as immune checkpoint inhibitors (ICIs), cancer vaccines, adoptive cell therapy (ACT), and combination therapies, have shown promise in enhancing anti-tumor responses. Dual ICI combinations, ICIs with molecular targeted drugs, and integration with local treatments or radiotherapy have demonstrated improved outcomes in HCC patients. This review highlights the evolving understanding of the immune microenvironment and the therapeutic potential of immunotherapeutic strategies in HCC management.